Design and application of the dynamic detection platform for testing the micromechanical properties of agricultural products - Hao, Yifeng; Wang, Yongwei; Jiang, Qianjing; Zhang, Jing; Wang, Jun (International Journal of Agricultural and Biological Engineering, 2022)
The micromechanical properties of agricultural products can be used to formulate simulation models and optimize processing parameters for harvest, packaging, and storage. In this study, a detection platform was designed for conducting mechanical tests on different specimens at the tissue level. The system provided controllable and precise displacements; the relative error was less than ±1.0%. The displacement and force measurements were calibrated. Micromechanical tests of apple parenchyma tissues were conducted to evaluate the performance of the proposed platform. The stress-strain curves of the specimens and the micrographs of the microstructures can be obtained simultaneously during the tests. The proposed platform has the capability to test mechanical properties and obtain micro behaviors of agricultural products at the tissue level, which helps in studying the failure mechanism of agricultural products under external loading. Keywords: elasticity module, micro tensile, parenchyma tissue, micromechanical properties, agricultural products DOI: 10.25165/j.ijabe.20221506.6548 Citation: Hao Y F, Wang Y W, Jiang Q J, Zhang J, Wang J. Design and application of the dynamic detection platform for testing the micromechanical properties of agricultural products. Int J Agric & Biol Eng, 2022; 15(6): 8–15.